Hemostatic and fibrinolytic status in patients with ovarian cancer and benign ovarian cysts: Could D-dimer and antithrombin III levels be included as prognostic markers for survival outcome? - Koh, S.C.L. (2016)
Clinical and Applied Thrombosis/Hemostasis